Analisis Pengelolaan Hutang Jangka Pendek terhadap Kelancaran Arus Kas pada UMKM Toko Madura di Kota Surabaya - Mahsa Alifyah Tsani; Jihan Bintang Angely; Sri Rahayuningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the management of short-term debt and its impact on cash flow smoothness in Toko Madura micro, small, and medium enterprises (MSMEs) in Surabaya City. Using a qualitative descriptive approach, the research was conducted through in-depth interviews and field observations at Toko Madura Barokah located in Pasar Wonokromo. The results show that short-term debt management is characterized by flexibility and trust-based relationships between store owners and suppliers, with payment terms ranging from 10 to 14 days. Debt management is carried out adaptively according to sales fluctuations and cash flow conditions. The average ratio of short-term debt to monthly cash flow is 17.2%, indicating that the debt level remains within a safe and manageable range. However, the financial recording system remains simple and lacks separation between personal and business finances, which may cause inaccuracies in cash control. Overall, short-term debt management contributes positively to cash flow stability through trust and payment discipline. Nevertheless, improving financial literacy and implementing a more structured accounting system are necessary to support sustainable business growth and better financial decision-making.